2008
DOI: 10.1161/circresaha.107.161067
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Causes Acute Lung Injury via αvβ5 and αvβ6 Integrin–Dependent Mechanisms

Abstract: Abstract-Interleukin (IL)-1␤ has previously been shown to be among the most biologically active cytokines in the lungs of patients with acute lung injury (ALI). Furthermore, there is experimental evidence that lung vascular permeability increases after short-term exposure to IL-1 protein, although the exact mechanism is unknown. Therefore, the objective of this study was to determine the mechanisms of IL-1␤-mediated increase in lung vascular permeability and pulmonary edema following transient overexpression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
140
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(141 citation statements)
references
References 31 publications
(34 reference statements)
0
140
1
Order By: Relevance
“…84 Several excellent recent reviews have addressed integrin-mediated activation of TGF-␤ in the lung. 85,86 In mouse models of lung injury using ␤6 integrin subunit-null mice, ␣v␤6 integrin-mediated TGF-␤ activation has been implicated in lung permeability changes (high tidal volume, 68 bleomycin, LPS, 87 and interleukin [IL]-1␤-induced 88 ), surfactant homeostasis, 80 and fibrosis (bleomycin-and radiation-induced 27 ). Mechanisms involving alveolar/endothelial cell junction formation in lung permeability or epithelial mesenchymal transition in fibrosis have been proposed (Figure 2).…”
Section: Lungmentioning
confidence: 99%
See 2 more Smart Citations
“…84 Several excellent recent reviews have addressed integrin-mediated activation of TGF-␤ in the lung. 85,86 In mouse models of lung injury using ␤6 integrin subunit-null mice, ␣v␤6 integrin-mediated TGF-␤ activation has been implicated in lung permeability changes (high tidal volume, 68 bleomycin, LPS, 87 and interleukin [IL]-1␤-induced 88 ), surfactant homeostasis, 80 and fibrosis (bleomycin-and radiation-induced 27 ). Mechanisms involving alveolar/endothelial cell junction formation in lung permeability or epithelial mesenchymal transition in fibrosis have been proposed (Figure 2).…”
Section: Lungmentioning
confidence: 99%
“…Mechanisms involving alveolar/endothelial cell junction formation in lung permeability or epithelial mesenchymal transition in fibrosis have been proposed (Figure 2). 88,89 Less is know of the role of the integrin ␣v␤6 in the airway. In vitro, integrin ␣v␤6-mediated TGF-␤ activation may play a role in promoting squamous metaplasia of airway epithelial cells.…”
Section: Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytokine interleukin-1␤ (IL-1␤) has been identified as a central mediator of epithelial permeability, ALI, and pulmonary fibrosis (23)(24)(25)(26)(27)(28)(29). Given that IL-1␤ and HER2 activation have both been implicated in the pathogenesis of lung injury, an interaction between the two signaling pathways is possible.…”
mentioning
confidence: 99%
“…Recently, Ganter et al demonstrated a complete inhibition of pulmonary edema using anti-αvβ6 integrin and anti-TGF-antibodies in IL-1 instilled ALI model. 21 …”
Section: Alveolar Epithelial Integrin Receptors: Pulmonary Edemamentioning
confidence: 99%